Brusatol Inhibits Esophageal Squamous Cell Carcinoma Tumorigenesis Through Bad-Mediated Mitochondrial Apoptosis Induction and Anti-Metastasis by Targeting Akt1 - Yao Ji; Xinxin Zhu; Yi Shi; Rui Fang; Yimeng Sun; Yurong Ruan; Liying Zhou; Yuanyuan Ge; Qichao Luo; Junyan Zhang; Junting Ma (Biomolecules)
Esophageal squamous cell carcinoma (ESCC) is a prevalent malignancy characterized by poor prognosis and a deficiency of effective therapies. Brusatol (Bru), a bioactive component derived from Brucea javanica, exhibits potent anti-tumor activity. However, the pro-apoptotic and anti-metastatic effects of Bru in ESCC remain unclear. ESCC cells were incubated with Bru. The apoptotic status and metastatic capacities of the cells was measured by the Annexin V-FITC/PI, and wound-healing and transwell assays. Potential targets of Bru in ESCC were identified. The mechanisms by which Bru exerts its effects in ESCC cells were explored. Additionally, the typical 4-NQO-induced ESCC mouse model was employed to examine the anti-tumor effect of Bru in vivo. In this study, Bru was found to trigger mitochondria-mediated cell apoptosis (approximately 5.9- and 3.3-fold increases in the level of apoptosis at high concentrations (80 nM) in the KYSE30 and KYSE450 cells) and inhibit metastasis (49% wound closure decreases at high concentrations (80 nM) in both cells, compared to that in the DMSO group) in ESCC cells. In vivo, Bru significantly suppressed ESCC tumorigenesis. Notably, Bru interacts with Akt1, leading to a reduction in the phosphorylation level of Akt1 at Ser473. Consequently, this not only induced dephosphorylation of Bad at the Ser136 residue to promote mitochondrial apoptosis but also inhibited metastasis in ESCC cells. Bru promoted Bad-mediated mitochondrial apoptosis and inhibited the ESCC cell metastasis by targeting Akt1. Our results suggest Bru is a novel Akt1 inhibitor for inhibiting the progression of ESCC.